Optimizing Character Building to Prevent Sexual Violence and Bullying in Universities - Susilowati, Susilowati - (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2025)
This This community service aimed to optimize character building implementation among students as a preventive effort against bullying and sexual violence in higher education. The activity was carried out by the Integrated Service Unit for Sexual Violence and Bullying (ULTKSP) at Universitas Brawijaya through counseling, mentoring, and student engagement programs that emphasized awareness, empathy, and responsible behavior. The qualitative descriptive method supported by questionnaires was used to identify types of bullying and assess the impact of character-building activities on students’ attitudes and interactions. A total of 400 students participated in the program. The results showed a decrease in physical, verbal, social, cyber, and sexual bullying, along with improved self-awareness, communication, and social interaction skills. This program demonstrated that strengthening character education through participatory and preventive approaches can effectively foster a safe, respectful, and inclusive campus environment.